Comparison of acute gastrointestinal toxicities between 3-dimensional conformal radiotherapy and intensity-modulated radiotherapy including prophylactic regions in chemoradiotherapy with S-1 for pancreatic cancer—importance of dose volume histogram parameters in the stomach as the predictive factors-. (20th August 2022) - Umezawa, Rei; Nakagawa, Kei; Mizuma, Masamichi; Katsuta, Yoshiyuki; Tanaka, Shohei; Kadoya, Noriyuki; Suzuki, Yu; Takeda, Kazuya; Takahashi, Noriyoshi; Yamamoto, Takaya; Unno, Michiaki; Jingu, Keiichi
Abstract: The purpose of this study was to compare acute gastrointestinal (GI) toxicities in patients who underwent 3-dimensional conformal radiotherapy (3DCRT) and intensity-modulated radiotherapy (IMRT) in chemoradiotherapy (CRT) with S-1 including prophylactic regions for pancreatic cancer. We also investigated the predictive factor of acute GI toxicities in dose volume histogram (DVH) parameters. Patients who received CRT with S-1 for pancreatic cancer between January 2014 and March 2021 were included. Radiotherapy (RT) with a total dose of 50-54 Gy was delivered. We examined the differences in the frequencies of acute GI toxicity of grade 2 or higher and DVH parameters of the stomach (ST) and duodenum (DU) between the 3DCRT group and the IMRT group. The RT-related predictive factors of acute GI toxicities were investigated by univariate and multivariate analyses. There were 25 patients in the 3DCRT group and 31 patients in the IMRT group. The frequencies of acute GI toxicity of G2 or higher were 36% in the 3DCRT group and 9.7% in the IMRT group (p = 0.035). ST V50 was the most predictive factor (p = 0.001), and the incidences of acute GI toxicity of G2 or higher in ST V50 ≥ 4.1 cc and < 4.1cc were 43.7% and 7.7%, respectively. ST V40 was also a significant predictive factor of acute GI toxicity (p = 0.002). IMRT could reduce acute GI toxicities in CRT with S-1 including prophylactic regions for pancreatic cancer. Acute GI toxicities may be affected by moderate to high doses to the ST.